1999
DOI: 10.1093/jn/129.11.2070
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplementation of Pregnant Mice Suppresses Heat-Induced Neural Tube Defects in the Offspring

Abstract: Neural tube defects (NTD) are a group of malformations that result from the failure of the neural tube to close early in embryonic development and among the most common congenital malformations in humans. It has been reported that a substantial proportion of NTD in humans can be prevented by folic acid (FA) supplementation prior to conception and during the first months of pregnancy, and myo-inositol (MI) was shown to reduce the incidence of NTD in curly tail mice which are not prevented by FA. Brief maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Folic acid has been shown to reduce the incidence of neural tube defects caused by valproic acid (Dawson et al, 2006;Padmanabhan and Shafiullah, 2003) retinoic acid (Reynolds et al, 2003;Firat et al, 2005), ochratoxin A (Katagiri et al 2007), Fumonisin B1 (Sadler et al, 2002), ethanol (Yanaguita et al, 2008), arsenic (Gefrides et al, 2002) and hyperthermia (Shin and Shiota, 1999;Li et al, 2003). Its role in the prevention of other congenital defects has not yet been fully explored.…”
Section: Discussionmentioning
confidence: 99%
“…Folic acid has been shown to reduce the incidence of neural tube defects caused by valproic acid (Dawson et al, 2006;Padmanabhan and Shafiullah, 2003) retinoic acid (Reynolds et al, 2003;Firat et al, 2005), ochratoxin A (Katagiri et al 2007), Fumonisin B1 (Sadler et al, 2002), ethanol (Yanaguita et al, 2008), arsenic (Gefrides et al, 2002) and hyperthermia (Shin and Shiota, 1999;Li et al, 2003). Its role in the prevention of other congenital defects has not yet been fully explored.…”
Section: Discussionmentioning
confidence: 99%
“…The present study relied on a third method: fetal rats were subjected to hyperthermal stress in utero on day 9.5 of pregnancy. Hyperthermia at this early stage of fetal period is known to cause brain malformations including anencephaly or exencephaly in rats (Edwards, 1968(Edwards, , 1986Mirkes, 1985;Webster et al ., 1985;Aoyama and Yamashina, 1994) and mice (Webster and Edwards, 1984;Chernoff and Golden, 1988;Seller and Perkins-Cole, 1987;Shiota,1988;Shin and Shiota, 1999). The results reported in this article will show the evidence that hyperthermia-induced exencephaly causes marked growth retardation of the adrenal cortex and a decreased population of somatotropes in the adenohypophysis.…”
Section: Introductionmentioning
confidence: 59%
“…The studies from the West have implicated maternal nutritional deficiency, especially of folate (and also vitamin B12 and zinc), as the likely cause of NTD [5][6][7][8][9][10][11]. Deficient folate levels may interfere with methylation processes and the process of closure of neural tube [9].…”
Section: Introductionmentioning
confidence: 99%
“…Deficient folate levels may interfere with methylation processes and the process of closure of neural tube [9]. Other studies have shown that folate metabolism is linked with that of homocysteine, methionine and cystathionine and that the micronutrients vitamin B12 and zinc are the co-factors in various reactions [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%